Isolation of phosphate solubilizing bacteria from root rhizosphere to supplement biofertilizer - Thi Thuy NGUYEN; The Anh LUU; Quang Trung DO (Acta Agriculturae Slovenica)
In soil, a large amount of supplemented phosphorus (P) are immediately transferred into insoluble forms and only 0.1 % of them is available for plant uptake. Therefore, exploring naturally occurring phosphate-solubilizing microorganisms is an essential activity to exploit them in reducing mineral phosphorus added to agricultural soils. In this study, we screened and isolated 7 bacteria that solubilized phosphate at different phosphate solubilization indexes, ranging from 4.2 to 226.1. Of them, the most efficient isolate is PSB31, which solubilized tri calcium phosphate (Ca3(PO4)2 at a rate of 962 mg l-1 and molecularly identified as Bacillus sp. (in: Bacteria) strain IMAU61039. This bacterial strain generated the low supernatant pH and the phosphatase, which are involved in the phosphorus solubilization mechanism. Furthermore, greenhouse experiments showed that tomato seedlings grown in PSB31-inoculated soil contained higher P amount and had much higher biomass than those plants grown in soil without PSB31 addition. These results suggest that the PSB31 strain has potential use as a biofertilizer.